Histopathology - Orchard, Guy; Nation, Brian (Fundamentals of biomedical science., 2012)
"Biomedical scientists are the foundation of modern healthcare, from cancer screening to diagnosing HIV, from blood transfusion for surgery to food poisoning and infection control. Without biomedical scientists, the diagnosis of disease, the evaluation of the effectiveness of treatment, and research into the causes and cures of disease would not be possible. The Fundamentals of Biomedical Science series is written to reflect the challenges of practicing biomedical science today. It draws together essential basic science with insights into laboratory practice to show how an understanding of the biology of disease is coupled to the analytical approaches that lead to diagnosis. Assuming only a minimum of prior knowledge, the series reviews the full range of disciplines to which a Biomedical Scientist may be exposed - from microbiology to cytopathology to transfusion science. Alongside volumes exploring specific biomedical themes and related laboratory diagnosis, an overarching Biomedical Science Practice volume gives a grounding in the professional and experimental skills with which any Biomedical Scientist must be equipped. The series Understands the complex roles of Biomedical Scientists in the modern practice of medicine Understands the development needs of employers and the Profession Addresses the need for understanding of a range of fundamental sciences in the context of Biomedicine Places the theoretical aspects of Biomedical Science in their practical context Histopatology describes the processes and practices that are central to the role of the histopathologist from pre-sampling to diagnosis to laboratory management. An understanding of the physiology of cells and tissue is vital for the successful identification of clinical conditions and, as such, this book beginnings by laying out the key features of both and their significance for diagnosis. But histopathology relies heavily on optical technology, and microscopy is covered in detail from fixing, through staining to light and electron imaging methods. A complete course on the concepts and skills needed for a biomedical scientist to work within a functioning histopathology laboratory. Online Resource Centre The Online Resource Centre to accompany Histopathology features: For registered adopters of the book: Figures from the book, available to download. For students: An interactive Digital Microscope, encouraging the exploration of tissue samples. Self-assessment modules to help you to check and reinforce understanding of the basic science introduced in each volume. Video podcasts including interviews with practicing biomedical scientists, and 'in the lab' footage showing biomedical science in practice"--Provided by publisher.